THE REALITY TEST IN FAMILY PARTNERSHIPS. - Landman, J. H. (The Accounting Review, 1950)
Abstract The United States Supreme Court in the recent Culbertson decision has unequivocally declared that the alternate tests of original contributed capital and vital services as supposedly set up in its earlier Tower and Lusthaus decisions are not decisive but only circumstantial evidence in determining the tax legality of family partnerships. The true test is the realism of the factual situation. The unequivocal Culbertson realism is a significant contribution to the solution of family partnership controversies. The earlier alternate arbitrary Tower and Lusthaus tests discriminated against a partnership interest and favored real estate, stocks and bonds. They held that the donating of real estate to create a tenancy by the entirety or a joint tenancy, or of stocks and bonds to organize a family corporation or an unrestricted family trust yields taxable income for the donees and not for the donor. On the other hand, an equally genuine donation of a partnership interest is valid for all purposes but its income is attributable to the donor when the asset originated with him.